Annotated record of the detailed examination of Mn deposits from DSDP Leg 21 (Sites 204, 205) - Robert E Burns; James E Andrews; Gerrit J van der Lingen; M Churkin; J S Galehouse; G H Packham; Thomas A Davies; James P Kennett; Paulian Dumitrica (PANGAEA, 1973)
The oceanic region between the Tonga-Kermadec Trench and New Zealand to the east and Australia to the west (see map at the back of this volume) has long been regarded as an anomalous region. Prior to development of the plate tectonic theory, it was known that the eastern boundary of the region was tectonically active, the western relatively passive. The DSDP Leg 21 overall objective was to provide initial coring data which would aid in reconstructing the tectonic history and relative plate movements of the Pacific and Indian crustal plates and determining the age of the tectonic features contained within the Tasman Sea region. In particular, the age and biostratigraphy of the oldest Pacific crustal section now being subducted into the Tonga-Kermadec Trench (Site 204) and the age and composition of the South Fiji Basin and of the basement rock (Site 205).
Supplement to: Burns, RE et al. (1973): Initial Reports of the Deep Sea Drilling Project,. U. S. Government Printing Office, XXI, 931 pp, https://doi.org/10.2973/dsdp.proc.21.1973